2013
DOI: 10.5578/mb.4138
|View full text |Cite
|
Sign up to set email alerts
|

Salmonella Pathogenicity Islands

Abstract: ÖZETSalmonella türleri fakültatif hücre içi yerleşim gösteren patojen bakterilerdir. Makrofajlara, dendritik ve epitelyal hücrelere invazyon yapabilmekte ve bütün Salmonella türleri patojen olarak kabul edilmektedir. İnvazyondan, hücre içinde canlılığını sürdürebilmesinden ve ekstraintestinal yayılımdan sorumlu olan virülans faktörlerini kodlayan genler Salmonella patojenite adaları (SPA) içinde yer alır. SPA'nın horizontal gen transferi ile kazanılmış olduğu düşünülmektedir. Bazı patojenite adaları Salmonella… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…Most of studies based on conventional molecular biology demonstrated that acquisition by HGT of Salmonella Pathogenicity Islands (SPIs) that contain genes coding for invasion, survival, and extraintestinal spread is among the prominent molecular mechanisms explaining the host adaptation of S. enterica subsp. enterica [22]. The 23 known SPIs are mainly involved in adhesion to epithelial cells (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Most of studies based on conventional molecular biology demonstrated that acquisition by HGT of Salmonella Pathogenicity Islands (SPIs) that contain genes coding for invasion, survival, and extraintestinal spread is among the prominent molecular mechanisms explaining the host adaptation of S. enterica subsp. enterica [22]. The 23 known SPIs are mainly involved in adhesion to epithelial cells (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…We found a high prevalence of virulence genes bcfC , ssaQ , and invA in both drug-susceptible and drug-resistant isolates ( Figure 1 ). As the majority of Salmonella virulence genes are located on Salmonella pathogenicity islands (SPIs) [ 42 , 43 ], it is expected that ssaQ , a gene located on an SPI that functions as a secretion system apparatus protein, is present in most of the isolates we analyzed. One invasion-related virulence gene, invA , was also expected to be present in the majority of the isolates, as previous studies have also found this gene to be present in most isolates [ 44 , 45 , 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…SPI-1 is required for the bacterium to invade the nonphagocytic epithelial cells, whereas SPI-2 is necessary for bacterial survival and replication inside the macrophages . The remaining SPIs contribute to other pathogenic attributes like fimbrial expression, magnesium and iron uptake, multiple antibiotic resistance, intracellular survival, and systemic dissemination …”
Section: Virulence Determinants Of Salmonella Pathogenesismentioning
confidence: 99%